Transforming Education in The Digital Age : How Technology Affects Teaching and Learning Methods - Agung Kurniawan S. Djibran; Paulus Subiyanto; Wakhudin Wakhudin; Nenden Sri Rahayu (PT. Anagata Sembagi Education, 2024)
The development of digital technology has brought significant changes to education, affecting teaching and learning methods. This article examines the impact of technology on education, especially in supporting more interactive, flexible and personalized learning. Various digital tools and platforms, such as online learning applications, educational software, as well as augmented reality and virtual reality technologies, enable more engaging and efficient learning experiences for learners. This research uses the literature study method to investigate scientific journal articles that discuss the transformation of learning in the digital era with the use of technology in modern education. The articles were selected based on criteria such as topic relevance, quality of research methodology and theoretical contribution. Searches were conducted in reputable academic databases such as Google Scholar and Sinta (Science and Technology Index) with the keywords